Enhanced IoT-based simulation for air handling unit (AHU) operational training - Razali, Nizamuddin; Ahmad Johar, Norfazirah; Abdul Jalil, Muhammad Zuhairi; Md Nor, Mohd Hairwan; Abdul Rahman, Khairul Anuar; Gerijih, Debie Devisser (2024)
In the evolving educational technology landscape, integrating Internet of Things (IoT) technologies transforms traditional teaching and learning approaches into more active, collaborative, and self-directed processes. This study introduces an advanced teaching solution to enhance engineering education, particularly in air conditioning and refrigeration: the IoT-embedded Simulation of Teaching Aids for Air Handling Unit (AHU) Operation. Utilising the comprehensive ADDIE instructional design model, this project progressed through five phases: analysis, design, development, implementation, and evaluation. The IoT integration facilitates real-time data monitoring and interactive learning experiences, offering a hands-on approach to understanding complex engineering concepts. Three domain experts rigorously evaluated the effectiveness of this teaching aid through a series of assessments focusing on design, development, and functionality. Feedback from these evaluations confirmed the teaching aid's success in engaging students and enhancing their learning process. Recognised for its quality materials, safety, and organised components, along with its innovative use of IoT technology, this product successfully fulfils the objectives of this study. It represents a significant step forward in modernising engineering education.